The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009 International Conference on Computers &Amp; Industrial Engineering 2009
DOI: 10.1109/iccie.2009.5223485
|View full text |Cite
|
Sign up to set email alerts
|

A modified Variable Neighborhood Search for minimizing the makespan on identical parallel machines

Abstract: Variable Neighborhood Search (VNS) is one of the most recent metaheuristics used for problem solving in which a systematic change of neighborhood within a local search is carried out. The idea is to build the best local search and shake operations based on neighbourhood structure available. In this paper, a modified version of VNS algorithm proposed for identical parallel machines scheduling problems with the objective function of minimizing makespan. The proposed VNS algorithm was tested 150 randomly generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In this section, the results of two versions of the proposed algorithm were compared with LPT [1], SA [17], GA [14], MVNS [21], and IVNS [23] algorithms from the literature. The two versions of the improved variable neighborhood search algorithms "HIVNS1 and RIVNS1" and "HIVNS2 and RIVNS2" were coded in MATLAB R2012a and executed on i5 CPU 5 GHz with 6 GB of RAM.…”
Section: Computational Results and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the results of two versions of the proposed algorithm were compared with LPT [1], SA [17], GA [14], MVNS [21], and IVNS [23] algorithms from the literature. The two versions of the improved variable neighborhood search algorithms "HIVNS1 and RIVNS1" and "HIVNS2 and RIVNS2" were coded in MATLAB R2012a and executed on i5 CPU 5 GHz with 6 GB of RAM.…”
Section: Computational Results and Comparisonmentioning
confidence: 99%
“…Computational results showed that hybridized DPSO (HDPSO) algorithm outperforms both SA and DPSO algorithms. Sevkli and Uysal [21] proposed modified variable neighborhood search (MVNS) which is based on exchange and move neighborhood structures. Computational results demonstrated that the proposed algorithm outperforms both GA and LPT algorithms.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The algorithm also employs two neighborhood structures to obtain improved solutions. Sevkli and Uysa [24] proposed a modified variable neighborhood search algorithm with two neighborhood structures for makespan minimization in identical parallel machine scheduling. The authors compared the proposed algorithm with the solutions of both the genetic algorithm and the LPT rule.…”
Section: Literature Reviewmentioning
confidence: 99%